Pengaruh Pelatihan dan Pemberian Insentif Terhadap Kinerja Karyawan UMKM dengan Intervening Motivasi Kerja - Hendarti, Amelia; Rahayu, Yayuk Ngesti (Magister Manajemen Universitas Wisnuwardhana, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in Indonesia's economic growth, particularly in the food and beverage processing sector. However, the sustainability and competitiveness of MSMEs depend heavily on the performance of their human resources. This study aims to analyze the effect of training and incentive provision on employee performance with work motivation as an intervening variable among MSMEs fostered by Bank Indonesia in Malang. This research employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through questionnaires distributed to employees of processed food and beverage MSMEs under the guidance of Bank Indonesia Malang. The results show that training has a positive and significant effect on employee performance. In contrast, incentives do not have a significant direct effect on employee performance. However, both training and incentives significantly influence work motivation. Work motivation also has a positive and significant effect on employee performance. Furthermore, mediation analysis reveals that work motivation does not mediate the relationship between training and employee performance, but successfully mediates the relationship between incentives and employee performance. These findings suggest that improving MSME human resource performance can be achieved through effective training programs and incentive systems that strengthen employee motivation. The study contributes to human resource management literature by explaining the mediating role of work motivation in the relationship between HR development practices and performance in MSMEs